Potential therapeutic hazards due to drug–drug interaction between topically and systemically coadministered medications - Lan MJ; Zhou Q (Dove Medical Press, 2013)
Mei-Juan Lan,1 Quan Zhou21Division of Nursing, 2Department of Pharmacy, the Second Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang Province, People's Republic of ChinaWe read with great interest the study by Peniston et al1 who performed a randomized controlled trial to examine the frequency and type of adverse events (AEs) in patients with osteoarthritis who received concurrent therapy of topical diclofenac sodium 1% gel (DSG), and drugs known to have potential drug–drug interactions (DDIs) with diclofenac; and concluded that such co-medication had little impact on the frequency of AEs in this population.    The results of this study1 provide very useful information for clinical practice, ie, DSG may be a safe alternative to oral diclofenac when a pain reliever needs to be co-medicated with CYP2C9 substrates like warfarin antidiabetic sulfonylurea derivatives. DDIs between topically and systemically coadministered medications are easily neglected by clinicians, which brings about potential risk of patient safety. Peniston et al1 answered a scientific question in clinical therapeutics. We completely appreciate their rigorous study and original spirit of exploration. We would like to discuss and share our perspectives in the following paragraphs.View original article by Peniston and colleagues